A primary care pharmacogenetic precision medicine pilot based on specific Māori tribal ethical frameworks and principles - Stephen P. Robertson; Benjamin J. Halliday; Rhonda Tibble; Caroline Koia; Tuta Haereroa; Elizabeth Goodin; Ben Curran; Claire E. Rye; Helen Wihongi; Ben Te Aika; Joep de Ligt; Donia Macartney-Coxson; et al. (Journal of Community Genetics, 2026)
Indigenous tribal communities are frequently underserved by genomic medicine because they are under-represented in research, often live in remote locations and have ethical and cultural perspectives that vary from westernised standpoints. The Rakeiora platform, a permissioning and analytical environment that incorporates Māori perspectives and ethical frameworks on how precision medicine research is best conducted was used to host a pharmacogenetic exemplar project to demonstrate proof of principle in a tribal community. The project was prospectively co-designed alongside community representatives through an extensive series of kanohi ki te kanohi (face-to-face) consultation hui, drawing on the strengths, insights, and aspirations of the community. Narratives socialising the study were metaphorically located in tribal-specific histories to improve participation. The cohort of 148 Māori individuals consented to have variants in CYP2C19 extracted from whole genome sequence datasets and correlated to the medicines they were prescribed and had dispensed over a 12-month period. Genotyping indicated that 7% of the cohort were genotypically predicted to be “poor metabolisers” and 11% “rapid metabolisers” of at least one drug known to be processed by CYP2C19. Based on international guidelines, 40% of prescriptions could have benefited from knowledge of the participant’s CYP2C19 genotype through either dose adjustment or prescription of an alternative drug. The study population was broadly supportive of research into precision medicine, but the majority wished to retain ongoing dynamic consent practices mediated by trusted local figures.

DAPP-MD: A multi-dimensional framework for adaptive planning under deep uncertainty and interacting risks - Patrick H. Curran; David R. Johnson; Tom M. Logan (Environmental Science & Policy, 2026)

Astaxanthin, meclizine, mitoglitazone, pioglitazone, alpha-ketoglutarate, mifepristone, methotrexate, and atorvastatin-telmisartan do not increase lifespan in UM-HET3 mice - Ron Korstanje; Randy Strong; Adam B. Salmon; Molly A. Bogue; Sean P. Curran; Vivian Diaz; Elizabeth Fernandez; Brett Ginsburg; Melissa Han; David E. Harrison; Catherine Kaczorowski; Matt Kaeberlein; et al. (GeroScience, 2026)

Bryophyte community composition is influenced by microhabitat and cover of vascular plants and lichens in New Zealand montane forest - Wendy Kentjens; David Glenny; Timothy J. Curran; Jon J. Sullivan (New Zealand Journal of Botany, 2025)

Increasing earthquake resilience for the power grid in southwestern British Columbia: integrated disaster planning for the shift from fuel to electric vehicles - Mike Churchill; David Bristow; Curran Crawford (Natural Hazards, 2024)

Damage to tropical forests caused by cyclones is driven by wind speed but mediated by topographical exposure and tree characteristics - Thomas Ibanez; David Bauman; Shin‐ichiro Aiba; Thomas Arsouze; Peter J. Bellingham; Chris Birkinshaw; Philippe Birnbaum; Timothy J. Curran; Saara J. DeWalt; John Dwyer; Thierry Fourcaud; Janet Franklin; et al. (Global Change Biology, 2024)
Each year, an average of 45 tropical cyclones affect coastal areas and potentially impact forests. The proportion of the most intense cyclones has increased over the past four decades and is predicted to continue to do so. Yet, it remains uncertain how topographical exposure and tree characteristics can mediate the damage caused by increasing wind speed. Here, we compiled empirical data on the damage caused by 11 cyclones occurring over the past 40 years, from 74 forest plots representing tropical regions worldwide, encompassing field data for 22,176 trees and 815 species. We reconstructed the wind structure of those tropical cyclones to estimate the maximum sustained wind speed (MSW) and wind direction at the studied plots. Then, we used a causal inference framework combined with Bayesian generalised linear mixed models to understand and quantify the causal effects of MSW, topographical exposure to wind (EXP), tree size (DBH) and species wood density ( ρ ) on the proportion of damaged trees at the community level, and on the probability of snapping or uprooting at the tree level. The probability of snapping or uprooting at the tree level and, hence, the proportion of damaged trees at the community level, increased with increasing MSW, and with increasing EXP accentuating the damaging effects of cyclones, in particular at higher wind speeds. Higher ρ decreased the probability of snapping and to a lesser extent of uprooting. Larger trees tended to have lower probabilities of snapping but increased probabilities of uprooting. Importantly, the effect of ρ decreasing the probabilities of snapping was more marked for smaller than larger trees and was further accentuated at higher MSW. Our work emphasises how local topography, tree size and species wood density together mediate cyclone damage to tropical forests, facilitating better predictions of the impacts of such disturbances in an increasingly windier world.

Drug Dissolution in Oral Drug Absorption: Workshop Report - Kimberly Raines; Payal Agarwal; Patrick Augustijns; Alaadin Alayoubi; Lucas Attia; Annette Bauer-Brandl; Martin Brandl; Parnali Chatterjee; Hansong Chen; Yuly Chiang Yu; Carrie Coutant; Ana Luisa Coutinho; et al. (The AAPS Journal, 2023)
The in-person workshop “Drug Dissolution in Oral Drug Absorption” was held on May 23–24, 2023, in Baltimore, MD, USA. The workshop was organized into lectures and breakout sessions. Three common topics that were re-visited by various lecturers were amorphous solid dispersions (ASDs), dissolution/permeation interplay, and in vitro methods to predict in vivo biopharmaceutics performance and risk. Topics that repeatedly surfaced across breakout sessions were the following: (1) meaning and assessment of “dissolved drug,” particularly of poorly water soluble drug in colloidal environments ( e.g. , fed conditions, ASDs); (2) potential limitations of a test that employs sink conditions for a poorly water soluble drug; (3) non-compendial methods ( e.g. , two-stage or multi-stage method, dissolution/permeation methods); (4) non-compendial conditions ( e.g. , apex vessels, non-sink conditions); and (5) potential benefit of having both a quality control method for batch release and a biopredictive/biorelevant method for biowaiver or bridging scenarios. An identified obstacle to non-compendial methods is the uncertainty of global regulatory acceptance of such methods.

One bat’s waste is another man’s treasure: a DNA metabarcoding approach for the assessment of biodiversity and ecosystem services in Ireland using bat faeces - Thomas G. Curran; Samuel S. Browett; David O’Neill; Aidan O’Hanlon; Catherine O’Reilly; Andrew P. Harrington; Allan D. McDevitt; Denise B. O’Meara (Biodiversity and Conservation, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Assessing the full costs of floodplain buyouts - William Curran-Groome; Hallee Haygood; Miyuki Hino; Todd K. BenDor; David Salvesen (Climatic Change, 2021)

Primer biases in the molecular assessment of diet in multiple insectivorous mammals - Samuel S. Browett; Thomas G. Curran; Denise B. O’Meara; Andrew P. Harrington; Naiara Guimarães Sales; Rachael E. Antwis; David O’Neill; Allan D. McDevitt (Mammalian Biology, 2021)
Our understanding of trophic interactions of small insectivorous mammals has been drastically improved with the advent of DNA metabarcoding. The technique has continued to be optimised over the years, with primer choice repeatedly being a vital factor for dietary inferences. However, the majority of dietary studies examining the effect of primer choice often rely on in silico analyses or comparing between species that occupy an identical niche type. Here, we apply DNA metabarcoding to empirically compare the prey detection capabilities of two widely used primer sets when assessing the diets of a flying (lesser horseshoe bat; Rhinolophus hipposideros ) and two ground-dwelling insectivores (greater white-toothed shrew; Crocidura russula and pygmy shrew; Sorex minutus ). Although R. hipposideros primarily rely on two prey orders (Lepidoptera and Diptera), the unique taxa detected by each primer shows that a combination of primers may be the best approach to fully describe bat trophic ecology. However, random forest classifier analysis suggests that one highly degenerate primer set detected the majority of both shrews’ diet despite higher levels of host amplification. The wide range of prey consumed by ground-dwelling insectivores can therefore be accurately documented from using a single broad-range primer set, which can decrease cost and labour. The results presented here show that dietary inferences will differ depending on the primer or primer combination used for insectivores occupying different niches (i.e., hunting in the air or ground) and demonstrate the importance of performing empirical pilot studies for novel study systems.

Comparison of Oyster Aquaculture Methods and Their Potential to Enhance Microbial Nitrogen Removal From Coastal Ecosystems - Paraskevi Mara; Virginia P. Edgcomb; Taylor R. Sehein; David Beaudoin; Chuck Martinsen; Christina Lovely; Bridget Belcher; Rebecca Cox; Meghan Curran; Claire Farnan; Peter Giannini; Sarah Lott; et al. (Frontiers in Marine Science, 2021)
Coastal ecosystems are impacted by excessive nutrient inputs that cause degradation of water quality and impairments of ecosystem functioning. Regulatory and management efforts to enhance nutrient export from coastal ecosystems include sustainable oyster aquaculture that removes nitrogen in the form of oyster biomass and increases particulate export to underlying sediments where increased organic material may enhance microbial denitrification. To better understand the impacts of oyster aquaculture on nitrogen removal, we examined bacterial processes in sediments underlying three of the most common aquaculture methods that vary in the proximity of oysters to the sediments. Sediment samples underlying sites managed with these different aquaculture methods were examined using the 16S rRNA gene to assess microbial community structure, gene expression analyses to examine nitrogen and sulfur cycling genes, and nitrogen gas flux measurements. All sites were located in the same hydrodynamic setting within Waquoit Bay, MA during 2018 and 2019. Although sediments under the different oyster farming practices showed similar communities, ordination analysis revealed discrete community groups formed along the sampling season. Measured N 2 fluxes and expression of key genes involved in denitrification, anaerobic ammonium oxidation (anammox), and dissimilatory nitrate reduction to ammonium (DNRA) increased during mid-summer and into fall in both years primarily under bottom cages. While all three oyster growing methods enhanced nitrogen removal relative to the control site, gene expression data indicate that the nitrogen retaining process of DNRA is particularly enhanced after end of July under bottom cages, and to a lesser extent, under suspended and floating bags. The choice of gear can also potentially increase processes that induce nitrogen retention in the form of ammonia in the underlying sediments over time, thus causing deviations from predicted nitrogen removal. If nitrogen removal is a primary objective, monitoring for these shifts is essential for making decisions about siting and size of aquaculture sites from year to year.

Alcohol attention bias in 14-16 year old adolescents: an eye tracking study - Casey McGivern; David Curran; Donncha Hanna (Psychopharmacology, 2021)
Rationale Theoretical models regarding the automaticity of attentional processes highlight a progression of attentional bias style from controlled to automatic in drinking populations as alcohol use progresses. Previous research has focused on older adolescent and adult drinking populations at later stages in their drinking career. Objectives The aim of this study was to investigate alcohol attention bias in 14–16-year-old adolescent social drinkers and abstainers. Methods Alcohol attention bias was measured in social drinking and abstaining groups in an eye-tracking paradigm. Questionnaires measured alcohol use, expectancies, exposure and socially desirable response styles. Results Social drinkers fixated to alcohol stimuli more frequently and spent a larger proportion of their fixation time attending to alcohol stimuli compared to non-drinkers. Groups displayed differences in their style of attentional processing of alcohol-related information, with heavy drinkers fixating significantly longer to alcohol information across alcohol stimulus presentation and exhibiting a delayed disengagement style of alcohol attention bias that differentiated them from light drinking and abstaining peers. All social drinkers fixated significantly more than abstainers in the latter half of alcohol stimulus presentation. Conclusion Alcohol attention bias was present in this adolescent sample. Drinking subgroups are defined from abstaining peers by unique features of their attentional bias that are controlled in nature. These findings are comparable to those in other adolescent and adult social drinking populations. The identification of specific attentional bias features according to drinking subpopulations has implications for our theoretical understanding of developing alcohol attention bias and problematic drinking behaviours, as well as at-risk identification and early intervention.

Dissolution Testing in Drug Product Development: Workshop Summary Report - Andreas Abend; David Curran; Jesse Kuiper; Xujin Lu; Hanlin Li; Andre Hermans; Pramod Kotwal; Dorys A. Diaz; Michael J. Cohen; Limin Zhang; Erika Stippler; German Drazer; et al. (The AAPS Journal, 2019)

A reproductive and developmental screening study of the fungal toxin ochratoxin A in Fischer rats - Genevieve S. Bondy; Laurie Coady; Nikia Ross; Don Caldwell; Anne Marie Gannon; Keri Kwong; Stephen Hayward; David E. Lefebvre; Virginia Liston; Jayadev Raju; Peter Pantazopoulos; Ivan Curran (Mycotoxin Research, 2018)

Age-related differences in alcohol attention bias: a cross-sectional study - Annie Melaugh McAteer; Donncha Hanna; David Curran (Psychopharmacology, 2018)

Life cycle assessment of photovoltaic manufacturing consortium (PVMC) copper indium gallium (di)selenide (CIGS) modules - Shanika Amarakoon; Cyril Vallet; Mary Ann Curran; Pradeep Haldar; David Metacarpa; David Fobare; Jennifer Bell (The International Journal of Life Cycle Assessment, 2018)

Psychedelics and related drugs: therapeutic possibilities, mechanisms and regulation - H. Valerie Curran; David Nutt; Harriet de Wit (Psychopharmacology, 2018)

Acute and chronic effects of cannabinoids on effort-related decision-making and reward learning: an evaluation of the cannabis ‘amotivational’ hypotheses - Will Lawn; Tom P Freeman; Rebecca A Pope; Alyssa Joye; Lisa Harvey; Chandni Hindocha; Claire Mokrysz; Abigail Moss; Matthew B Wall; Michael AP Bloomfield; Ravi K Das; Celia JA Morgan; et al. (Psychopharmacology, 2016)

Alcohol attention bias in adolescent social drinkers: an eye tracking study - Annie Melaugh McAteer; David Curran; Donncha Hanna (Psychopharmacology, 2015)

Heritable changes in regional cortical thickness with age - Francois Chouinard-Decorte; D. Reese McKay; Andrew Reid; Budhachandra Khundrakpam; Lu Zhao; Sherif Karama; Pierre Rioux; Emma Sprooten; Emma Knowles; Jack W. Kent; Joanne E. Curran; Harald H. H. Göring; et al. (Brain Imaging and Behavior, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Influence of age, sex and genetic factors on the human brain - D. Reese McKay; Emma E. M. Knowles; Anderson A. M. Winkler; Emma Sprooten; Peter Kochunov; Rene L. Olvera; Joanne E. Curran; Jack W. Kent; Melanie A. Carless; Harald H. H. Göring; Thomas D. Dyer; Ravi Duggirala; et al. (Brain Imaging and Behavior, 2014)

Population pharmacokinetics of intravenous acetaminophen and its metabolites in major surgical patients - Katie H. Owens; Philip G. M. Murphy; Natalie J. Medlicott; Julia Kennedy; Mathew Zacharias; Neil Curran; Sree Sreebhavan; Mark Thompson-Fawcett; David M. Reith (Journal of Pharmacokinetics and Pharmacodynamics, 2014)

Levisunguis subaequalis n. g., n. sp., a tongue worm (Pentastomida: Porocephalida: Sebekidae) infecting softshell turtles, Apalone spp. (Testudines: Trionychidae) in the southeastern United States - Stephen S. Curran; Robin M. Overstreet; David E. Collins; George W. Benz (Systematic Parasitology, 2014)

Late Pleistocene and early Holocene change in the Weddell Sea: a new climate record from the Patriot Hills, Ellsworth Mountains, West Antarctica - CHRIS TURNEY; CHRIS FOGWILL; TAS D. VAN OMMEN; ANDREW D. MOY; DAVID ETHERIDGE; MAURO RUBINO; MARK A. J. CURRAN; ANDRÉS RIVERA (Journal of Quaternary Science, 2013)
The transition from the late Pleistocene to the Holocene (30 000–5000 years ago) was a period of considerable climate variability, which has been associated with changes in deep water formation and the intensity of the Meridional Overturning Circulation. Although numerous records exist across the North Atlantic region, few Antarctic ice core records have been obtained from the south. Here we exploit the potential of upwelling ancient ice – so‐called blue ice areas (BIAs) – from the Patriot Hills in the Ellsworth Mountains to derive the first deuterium isotope record (δD) from continental Antarctica south of the Weddell Sea. Gas analysis and glaciological considerations provide a first relative chronology. Inferred temperature trends from the Patriot Hills BIA and snow pit suggest changing climate influences during the transition between the last glacial period and Holocene. Under modern conditions, the interplay between the Antarctic high‐pressure system and the Southern Annular Mode appears to play a significant role in controlling katabatic wind flow over the site while the BIA record suggests that greater sea ice extent during the last glacial period was a major control. Our results demonstrate the considerable potential of the Patriot Hills site for reconstructing past climate change in the south Atlantic region.

Informing future cartilage repair strategies: a comparative study of three different human cell types for cartilage tissue engineering - Sushmita Saha; Jennifer Kirkham; David Wood; Stephen Curran; Xuebin B. Yang (Cell and Tissue Research, 2013)

Linkage to chromosome 2q36.1 in autosomal dominant Dandy-Walker malformation with occipital cephalocele and evidence for genetic heterogeneity - Ali Jalali; Kimberly A. Aldinger; Ajit Chary; David G. Mclone; Robin M. Bowman; Luan Cong Le; Phillip Jardine; Ruth Newbury-Ecob; Andrew Mallick; Nadereh Jafari; Eric J. Russell; John Curran; et al. (Human Genetics, 2008)

Effects of partial throughfall exclusion on the phenology of Coussarea racemosa (Rubiaceae) in an east-central Amazon rainforest - Paulo Brando; David Ray; Daniel Nepstad; Gina Cardinot; Lisa M. Curran; Rafael Oliveira (Oecologia, 2006)

Woody debris contribution to the carbon budget of selectively logged and maturing mid-latitude forests - Wendy H. Liu; David M. Bryant; Lucy R. Hutyra; Scott R. Saleska; Elizabeth Hammond-Pyle; Daniel Curran; Steven C. Wofsy (Oecologia, 2006)

Modeling the Sustainability of Subsistence Farming and Hunting in the Ituri Forest of Zaire - David S. Wilkie; Bryan Curran; Richard Tshombe; Gilda A. Morelli (Conservation Biology, 1998)

Modeling the Sustainability of Subsistence Farming and Hunting in the Ituri Forest of Zaire - David S. Wilkie; Bryan Curran; Richard Tshombe; Gilda A. Morelli (Conservation Biology, 1998)
We used empirical data to simulate the impacts, over the next 40 years, of subsistence‐level agricultural clearing and bushmeat consumption on forest resources within the recently established Okapi Wildlife Reserve in northeastern Zaire. Satellite imagery, human population census data, and field measurements were used to calculate present and projected impacts of agricultural clearing on forest cover. Data on per capita meat consumption and the species captured by hunters were combined with relevant ecological data to estimate ratios of consumption to production and to assess the sustainability of hunting. Even with projected population growth of nearly 300% among local communities over 40 years, sufficient secondary forest is available that agricultural clearing will have minimal effect on mature forest throughout most of the reserve. Impacts on the reserve’s fauna will be more dramatic, particularly within 15 km of villages, where most hunting currently occurs. Subsistence exploitation of forest antelopes may be sustainable in much of the reserve (especially if high estimates of game production are used), but as the human population continues to increase duikers will likely be over‐hunted. Primate populations do not appear to be threatened in the near future in those areas where bow hunters exploit monkeys, but an increase in this specialized activity in other regions of the reserve and growing human populations could change this. Although additional surveys of commonly hunted species throughout the Okapi Wildlife Reserve are essential to enhancing the precision of the simulation, our results suggest that mitigation efforts should be designed and implemented now if the long‐term effects of domestic bushmeat consumption are to be addressed. Modelado de la Sustentabilidad de Cosecha y Caza de Subsistencia en el Bosque Ituri en Zaire Utilizamos datos empíricos para simular los impactos del nivel de persistencia de clareo agricultural y el consumo de carne silvestre en los recursos forestales durante los próximos 40 años, dentro de la recientemente establecida reserva de vida silvestre Okapi en el noreste de Zaire. Imágenes de satélite, datos de censos poblacionales humanos y mediciones de campo fueron usados para calcular los impactos actuales y proyectados del clareo agricultural en la cobertura del bosque. Datos de consumo de carne per cápita y de las especies capturadas por caza fueron combinados con datos ecológicos relevantes para estimar la relación del consumo con la producción y para evaluar la sustentabilidad de la caza. Aún con el crecimiento poblacional proyectado de cerca de un 300% a lo largo de 40 años entre las comunidades locales, existe suficiente bosque secundario viable de tal manera que el clareo agricultural tendrá efectos mínimos sobre el bosque maduro a lo largo de la mayoría de la reserva. Impactos en la fauna de la reserva serán mas dramáticos, particularmente dentro de los 15 km de villas, donde la mayorá de la caza se lleva a cabo actualmente. La explotación de subsistencia de antílopes del bosque podría ser sustentable en gran parte de la reserva (especialmente si se utilizan estimaciones de producción cinegética), pero en vista de que la población humana continúa incrementando, algunos antílopes podrían ser sobre‐cazados. Las poblaciones de primates no parecen estar amenazadas a corto plazo en aquellas áreas donde los cazadores con arco capturan los monos, pero un incremento en esta actividad especializada en otras regiones de la reserva, aunado al crecimiento poblacional humano podría cambiar esta situación. Aunque estudios adicionales sobre las especies comunmente cazadas en la reserva Okapi son escenciales para incrementar la precisión de la simulación, nuestros resultados sugieren que los esfuerzos de mitigación deberán ser diseñados e implementados ahora si es que se pretenden abordar los impactos a largo plazo del consumo de carne silvestre.